Hábitos de estudio y rendimiento académico en estudiantes de enfermería de la Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Vigay Flores, Clemente (2022)
The objective of the research was to determine the relationship between study habits and academic performance in nursing students, from the National University of the Peruvian Amazon, the method was quantitative, non experimental design. The population was 250 students from the UNAP Nursing Faculty studying levels between the first and fourth academic level and the sample was 152. The technique used was the documentary review and the survey. The instruments were the CAMS 85 study Habits Inventory and the academic performance scorecard, the statistical test was chi square (X2) with a significance leve lof 95% with alpha ? 0.05. The results indicate that 67% of students were between the ages of 17 and 21, 77,6% were female, 82,9% are only dedicated to studying, 73% have a negative tendency towards their habits for study and 83,6% presente dan inadequate leve lof their study habits and 96,7% presented Good and regular academic performance and 3,3% presented a very Good acazdemic performance. Conclusión, through Kendall’s tB test, with a confidence leve lof 95%, and significant (p < 0,05) a p = 0,000 and calculated Kendall’s tB value of 0,303, with which the hypothesis is accepted there is a statistically significant relationship between study habits and academic performance of nursing students.